1961
DOI: 10.1021/jo01066a067
|View full text |Cite
|
Sign up to set email alerts
|

Lesquerolic Acid. A New Hydroxy Acid from Lesquerella Seed Oil1a

Abstract: A major constituent of Lesquerella lasiocarpa seed oil is characterized as (+)-14-hydroxy-cz's-l 1-eicosenoic acid. For convenience, it is called lesquerolic acid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

1962
1962
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(17 citation statements)
references
References 0 publications
1
16
0
Order By: Relevance
“…Although this bias could be attributed to differential metabolism of the hydroxy fatty acids, the fact that both of these ratios follow the same trend within the series of Lesquerella variants (more hydroxylation for LFAH-N149I, less hydroxylation for LFAH-N149T; data in 9 by LFAH gave the expected products. Nonetheless, the available data indicate that the stereospecificity of the FAD2 variants is consistent with that of the characterized FAD2 (19), LFAH (20), and CFAH (21).…”
Section: Analysis Of Variant Fad2 Genes-as Illustrated Insupporting
confidence: 69%
See 1 more Smart Citation
“…Although this bias could be attributed to differential metabolism of the hydroxy fatty acids, the fact that both of these ratios follow the same trend within the series of Lesquerella variants (more hydroxylation for LFAH-N149I, less hydroxylation for LFAH-N149T; data in 9 by LFAH gave the expected products. Nonetheless, the available data indicate that the stereospecificity of the FAD2 variants is consistent with that of the characterized FAD2 (19), LFAH (20), and CFAH (21).…”
Section: Analysis Of Variant Fad2 Genes-as Illustrated Insupporting
confidence: 69%
“…The Lesquerella enzyme must also share this same stereospecificity, as the seed oil-derived lesquerolic acid retains the same optical rotation properties as ricinoleic acid derived from castor seed oil (20). The knowledge that these enzymes are highly homologous (1,2) and that the enzymes catalyze both desaturation and hydroxylation, just with differing product ratios, implies that these enzymes employ closely related catalytic mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…The goal of the screening program was to find new or unusual kinds of oils that will not compete with vegetable oils [10]. The unique hydroxy fatty acids (HFA) from lesquerella seeds were identified [10][11][12] and the crop's potential for high yield was likewise recognized. During the 1960s when no Lesquerella species had been cultivated, it is reported that the original plant collectors of Lesquerella species used a combine method in deserts of Texas to collect large quantities of seed from wild populations for initial research activities [13].…”
Section: Introductionmentioning
confidence: 99%
“…Lesquerolic acid (14-hydroxy-eicosa-11-enoic, 14-OH-20:1) content in the seed oil of P. fendleri and other species is between 45 and 55 % of the total HFA [15]. Lesquerolic acid was first isolated and identified in P. fendleri's sister species P. lasiocarpa and P. lindheimeri [11]. The species P. lindheimeri has about 89 % lesquerolic acid content.…”
Section: Introductionmentioning
confidence: 99%
“…analysis of the acidic oxidation products obtained from unsaturated fatty acids and esters has confirmed the quasi-quantitative oxidation t o predictable end products (5)(6)(7). This aspect has made the reagent highly successful in routine analysis of lipids (6)(7)(8)(9)(10) as well as in locating the position of double bonds in unknown or isomeric unsaturated fatty acids (6,7,(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%